Формування економічного механізму управління інвестиційно-інноваційною діяльністю будівельних підприємств - Федотова, С. Ю. (Ways to Improve Construction Efficiency, 2012)
The purpose of this article is to develop a structural dynamic model of Investment innovation activity of construction company, which provides for the formation of economic management mechanism, followed by its implementation in the control profit.